An assessment of spatial and temporal variation of sulfur dioxide levels over Istanbul, Turkey - (:unkn) unknown (ELSEVIER SCI LTD, 2000)
Sulfur dioxide concentration levels are investigated in Istanbul to assess air pollution during the heating seasons in which the concentration of air pollutants reach high levels due to the consumption of low-quality fossil fuels. Results reveal that in the 1985-91 period there is an increasing trend in the concentrations of air pollutants. One reason for this increase is found to be the switching to use of low-quality fossil fuels instead of cleaner ones; the consumption ratio of coal/fuel-oil increased drastically in the 1980s from the ratio of 0.62 during 1980 to 3.09 by 1990. Linear regression analysis also indicated the similar variability of sulfur dioxide and particulate matter curves with a correlation coefficient R-2 = 0.87. An optimum interpolation technique, kriging, is used to obtain the spatial distribution of sulfur dioxide over the area. Results indicated that the maximum concentration regions over the European side, exceeding 300 mu g/m(3) monthly averages, are found to be the Fatih-Gaziosmanpasa-Bayrampasa, Beyoglu-Sisli, and Eminonu areas. On the Asian side, the Goztepe-Kadikoy area received a major threat from sulfur dioxide pollution. Results also indicated that there was a considerable decrease in air pollution levels over Istanbul in the 1995-96 season compared with the previous two seasons. This can be explained by (1) the increase in ventilation, (2) switching to natural gas as a home and business heating fuel, and (3) treatment of coal before its entrance to the city. The variability in weather conditions is explained by the adoption of a ventilation index, which is the product of wind speed and inversion height. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: air pollution; sulfur dioxide; fossil fuels; Istanbul; kriging; ventilation coefficient; CLIMATE-CHANGE; URBANIZATION